2017
DOI: 10.3892/ol.2017.5906
|View full text |Cite
|
Sign up to set email alerts
|

New role of human ribosomal protein S3: Regulation of cell cycle via phosphorylation by cyclin-dependent kinase 2

Abstract: Human ribosomal protein S3 (hRpS3) is a component of the 40S ribosomal subunit that associated in protein synthesis. hRpS3 has additional ribosomal functions such as DNA repair, transcription, metastasis, and apoptosis via interaction with numerous signaling molecules and has different modifications. Cyclin-dependent kinases (CDKs) are heterodimeric serine/threonine protein kinases that regulate cell cycle progression. Among its members, the Cdk1-cyclin B complex is known to control cell progression in the G2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We have previously reviewed evidence for autologous regulation of most ribosomal proteins of their own translation by means of binding directly to their own mRNA [7], and they include only a summary of that information in Table 3, Table 4, Table 5 and Table 6. The majority of ribosomal proteins, both in prokaryotes and eukaryotes, play additional roles in cellular metabolism, ranging from DNA repair, control of transcription and replication, and histone binding to the regulation of various enzymes and mRNA splicing as summarized in Table 3, Table 4, Table 5 and Table 6 [81,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112]. The degree to which these extra-ribosomal functions are integrated into cellular functions is exemplified by the participation of riboprotein L13a into the GAIT complex in eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reviewed evidence for autologous regulation of most ribosomal proteins of their own translation by means of binding directly to their own mRNA [7], and they include only a summary of that information in Table 3, Table 4, Table 5 and Table 6. The majority of ribosomal proteins, both in prokaryotes and eukaryotes, play additional roles in cellular metabolism, ranging from DNA repair, control of transcription and replication, and histone binding to the regulation of various enzymes and mRNA splicing as summarized in Table 3, Table 4, Table 5 and Table 6 [81,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112]. The degree to which these extra-ribosomal functions are integrated into cellular functions is exemplified by the participation of riboprotein L13a into the GAIT complex in eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…The other possibility is that accumulation of SUMOylated RPL30 has an extra-ribosomal function. Many ribosomal proteins in plant and animal systems have been reported to have specialized functions other than translation (Warner and McIntosh, 2009;Nagaraj et al, 2015;Han et al, 2017;Li et al, 2017;Zhang et al, 2017;Dionne et al, 2019). Moreover, SUMO conjugation of mouse RPL11 protein has been shown to regulate p53-mediated stress responses (El Motiam et al, 2018), further supporting the importance of SUMOylation on the extraribosomal functions of ribosomal proteins.…”
Section: Chlamydomonasmentioning
confidence: 99%
“…Studies in Caenorhabditis elegans have shown that it is not uncommon 332 among ribosomal proteins to be AS-NMD targets [25]. In particular, ribosomal proteins L3, L10a, and 333 L12 use an evolutionarily-conserved pathway to insert PTCs in their pre-mRNA [76][77][78]. Here we show 334 that exon 2 of RPS3 has an alternative upstream donor site that induces a frameshift and targets RPS3 335 pre-mRNA for degradation ( Figure 4c).…”
mentioning
confidence: 73%
“…Human ribosomal protein S3 (RPS3) is a component of the 40S ribosomal subunit that is mainly associated 330 with protein synthesis. However, RPS3 has many additional extraribosomal functions and is involved in 331 apoptosis and tumorigenesis [76]. Studies in Caenorhabditis elegans have shown that it is not uncommon 332 among ribosomal proteins to be AS-NMD targets [25].…”
mentioning
confidence: 99%